Teaching a concept with GeoGebra: Periodicity of trigonometric functions* - Ibrahim, Kepceoğlu; llyas, Yavuz (Academic Journals, 2016)
Being one of the major subjects in high school mathematics curriculum, trigonometry links algebraic, geometric and graphical reasoning. The aim of this study is to investigate the effect of GeoGebra in the teaching of the concept of the periodicity of trigonometric functions.  In this study, it is investigated how effective is the dynamic mathematics software GeoGebra being used in the teaching of the periodicity of trigonometric functions, which is taught based on “formulas” in the context of “traditional” mathematics education. The aim is to analyze and to compare the effect of the traditional teaching and the computer assisted mathematics teaching on students’ conceptual learning about the periodicity of trigonometric functions. The design of this study is chosen as a quasi-experimental, and the working group is 36 tenth grade high school students from a public high school in Istanbul. 15 days after the instruction period, participants filled in a 5 questions test. The answers of students are analyzed using descriptive statistics. According to the results of the study, with the aid of computer mathematics education is more effective on students’ learning than traditional mathematics education. Key words: GeoGebra, concept teaching, trigonometry, periodicity.
Keywords: 2. Zero hunger; 4. Education; 16. Peace & justice